Measuring Quality of Care: A Rasch Validity Analysis of the Good Nursing Care Scale - Stolt M; Katajisto J; Kottorp A; Leino-Kilpi H (My University, 2022)
BACKGROUND:
Patient-centeredness is emphasized in both health policies and practice, calling for reliable instruments for the evaluation of the quality of nursing care.
PURPOSE:
The purpose was to analyze the psychometric properties of the Good Nursing Care Scale (GNCS) in a sample of surgical patients and nurses.
METHODS:
An explorative cross-sectional study design was used. Data were collected with the 40-item GNCS from surgical patients (n = 476) and nurses (n = 167) in Finland. The data were analyzed with Rasch analysis.
RESULTS:
The GNCS provided evidence of unidimensionality with acceptable goodness-of-fit to the Rasch model in both samples. Person-separation validity was acceptable. Person misfit was reasonable. The Rasch-equivalent Cronbach α was 0.81 (patient data) and 0.88 (nurse data).
CONCLUSIONS:
The findings support that the GNCS is a psychometrically sound instrument that can be used in measuring the quality of nursing care, from the perspective of both patients and nurses.